Relationship Between Oral Health Behaviors and General Health Behaviors in a Japanese Adult Population - Akio Tada, DDS, PHD; Takashi Matsukubo, DDS, PHD (Blackwell Synergy, 2003)
The aim of this study was to analyze the relationship between oral health behaviors andgeneral health behaviors in adults